The Role of Bronchoscopic Cryoablation in Management of Central Airway Obstruction - Dicky Soehardiman; Rahma Ayu Indahati; Mia Elhidsi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Central airway obstruction is one of respiratory emergency manifested as dyspnea, stridor and obstructive pneumonia. Most of central airway obstruction cases were treated with resection and surgery. Bronchoscopy is an initial modality to diagnose, stabilize the airway obstruction and evaluate for palliative treatment. Cryoablation is an evolving therapeutic bronchoscopic methods. Through rapid freeze–thaw cycles, cryoablation causes cell death and tissue necrosis or tissue adherence that can be used via the flexible or rigid bronchoscope. Cryoablation can safely restore airway patency and improve symptoms in patients with central airways obstruction from exophytic tumours. It is also used in the treatment of granulation tissue and benign strictures. Clinical studies showed improvement of dyspnea, cough, and hemoptysis with non-significant complications.